Constitutionality of KPU members prohibited to be management of community organizations. A Study of the Constitutional Court Decision Number 31 / PUU-XVI/2018 - Yayuk Dwi Agus Sulistiorini,; Hufron,; Made Warka, (Technium Social Sciences Journal, 2021)
This research is a scientific activity that seeks to obtain a solution to a problem related to the prohibition of KPU (General Election Commission) members from being administrators of community organizations. This research is a normative legal research. The Court, in it’s ruling, decided it was unacceptable. And in accordance with the provisions of Article 60 of the Law of the Constitutional Court on the content of paragraphs, articles, and/or parts of laws that have been tested, a re-examination cannot be requested unless the content in the 1945 Constitution of the Republic of Indonesia which is used as the basis for testing is different. Therefore, regarding the provisions of Article 21 paragraph (1) letter k which is declared to be an open legal policy, it must be amended the article through a revision of the legislation.